Prognostic Value of 18F-FDG PET/CT Metabolic Parameters in Metastatic Differentiated Thyroid Cancers. (June 2015) - Masson-Deshayes, Soizic; Schvartz, Claire; Dalban, Cécile; Guendouzen, Sofiane; Pochart, Jean-Marie; Dalac, Audrey; Fieffe, Sandrine; Bruna-Muraille, Claire; Dabakuyo-Yonli, Tienhan Sandrine; Papathanassiou, Dimitri
Abstract : Purpose: To evaluate the prognostic value of 18 F-fluorodeoxyglucose positron emission tomography (FDG PET) with quantitative analysis using metabolic parameters in metastatic differentiated thyroid cancer (DTC). Materials and Methods: The FDG-PET scans of 37 patients with metastatic DTC were studied retrospectively. The number of FDG-avid lesions, the SUVmax, the SULpeak of the lesion with the highest FDG uptake, the overall metabolic tumor volume (MTV), and the total lesion glycolysis (TLG) were measured. Curves of progression-free survival (Kaplan-Meier) and Cox univariate and multivariate analyses determined the prognostic factors for survival. Results: Progression-free survival was better in patients with less than 10 FDG-avid lesions ( P = 0.0089), the SUVmax less than 10 ( P = 0.0026), the SULpeak less than 5 ( P = 0.0004), and the TLG less than 154 ( P = 0.0110). Cox analyses showed that only the result of the PET scan was predictive of survival (age, TNM stage, histology, and the 131 I whole body radioiodine scan were not associated with prognosis). In the univariate analysis, prognostic factors for progression-free survival and overall survival were the SUVmax ( P = 0.004; P = 0.018), the SULpeak ( P = 0.001; P = 0.017), and the TLG ( P = 0.014; P = 0.012). The number of FDG-avid lesions was significantly associated with progression-free survival ( P = 0.012), but not the MTV. In the multivariate analysis, the number of FDG-avid lesions and the SULpeak were independent prognostic factors. Conclusions: FDG PET using metabolic parameters is a prognostic factor in metastatic DTC. It could improve the therapeutic management and follow-up of patients.